2018
DOI: 10.1002/bbb.1951
|View full text |Cite
|
Sign up to set email alerts
|

US alternative jet fuel deployment scenario analyses identifying key drivers and geospatial patterns for the first billion gallons,

Abstract: The aviation sector's commitments to carbon‐neutral growth in international aviation starting in 2020, and the desire to improve supply surety, price stability, and the environmental performance of aviation fuels, have led to broad interest in sustainable alternative jet fuels. Here, we use the system‐dynamics‐based biomass scenario model (BSM), focused on alternative jet fuel production capacity evolution, and the geospatially explicit Freight and Fuel Transportation Optimization Tool (FTOT), focused on optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For real world costs as currently understood, researchers are implementing stochastic and deterministic TEA analysis assuming various policies and technology maturation rates to aid in thinking about uncertain future conditions (Tanzil, et al; Trejo-Pech et al). Other researchers are analyzing the influence of technoeconomics, technology maturation rates, and policies on deployment potential for SAF and other fuels (Newes, Han, & Peterson, 2017;Lewis, et al, 2018).…”
Section: Tools For Evaluating Saf and Saf Supply Chains-reducing Cost...mentioning
confidence: 99%
See 2 more Smart Citations
“…For real world costs as currently understood, researchers are implementing stochastic and deterministic TEA analysis assuming various policies and technology maturation rates to aid in thinking about uncertain future conditions (Tanzil, et al; Trejo-Pech et al). Other researchers are analyzing the influence of technoeconomics, technology maturation rates, and policies on deployment potential for SAF and other fuels (Newes, Han, & Peterson, 2017;Lewis, et al, 2018).…”
Section: Tools For Evaluating Saf and Saf Supply Chains-reducing Cost...mentioning
confidence: 99%
“…Other tools have been developed to identify supply chain development and deployment opportunities, including tools for siting biorefineries based on geographic variation in capital and operational costs and resource availability (e.g., (English et al) and how geography and transportation scenarios and disruptions influence supply chain performance (Lewis, et al, 2018). Social criteria, including social capital and cultural capital, should be considered when identifying the potential suitability of biorefinery candidate locations (Anderson et al).…”
Section: Tools For Evaluating Saf and Saf Supply Chains-reducing Cost...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the US, interest in SAF by the commercial aviation industry is mainly driven by petroleumbased jet fuel price instability, energy security, environmental performance, and the impending implementation of CORSIA for international flights [4]. Currently, at least two biorefineries are commercializing SAF in the US.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for growth of SAF consumption in the US depends upon several factors including feedstock availability, oil conversion technology, aviation industry demand, and overall supply chain profitability. Lewis et al [4] modeled SAF production capacity in the US and concluded that significant production and distribution of SAF are possible by 2030 if appropriate incentives, such as higher guarantee rates or higher renewable identification number (RIN) prices along with high oil prices and investment deployment are in place. Without substantial changes in current incentives, the authors conclude that between 0.76 and 10.22 billion liters of SAF could be produced and distributed by 2030, with simulations showing that 1 billion gallons could be produced by 2030 with a 38% probability.…”
Section: Introductionmentioning
confidence: 99%